The Story of Heathcliff’s Journey Back to Wuthering Heights de Lin Haire-Sargeant (1992), ou le « deux en un » de la ré-écriture - Isabelle Roblin (Revue LISA)
Lin Haire-Sargeant’s 1992 novel The Story of Heathcliff’s Journey Back to Wuthering Heights is typical of the interest shown by contemporary American writers in Victorian novels. It could indeed be classified doubly as a “retro-Victorian novel” since it partly re-writes not only Emily Brontë’s most famous novel, Wuthering Heights, as the title points out, but also, somewhat less obviously, Charlotte Brontë’s Jane Eyre. We will study in this article how Lin Haire-Sargeant’s attempt at re-writing highlights the usual aims of the retro-Victorian novel: taking advantage of the blanks left by the source novels to propose to the reader a modern critical approach, while at the same time being as faithful as possible to the writing conventions of the 19th century, and suggesting another point of view on a well-known story, through a postmodern mixing of historical and fictive characters.